Exploring the Social Empowerment of Women through SHG Approac - Avishek Saha , K. Pradhan , Rema Das; Victor Sarkar (Indian Journal of Extension Education, 2018)
Women play pivotal role in any developmental process within the society and they also participate actively in various social events. Therefore, it is imperative to empower women socially so that they can realize and make others aware of the social responsibilities appropriately and thereby raise their voice regarding various social issues related to women for betterment of the society. The Self Help Group approach can be an effective instrument for this purpose. Therefore, the present study has attempted to assess the status of social empowerment of the women after joining Self Help Group (SHG) and thereby, exploring different factors associated with their social empowerment. The study was conducted in four villages of the Coochbehar-I block in Coochbehar district of West Bengal. Purposive as well as multistage sampling and random sampling procedures were followed in selecting the respondents. The social empowerment of the women SHG members was considered as the dependent variable and the other attributes of the women respondents were considered as the independent variables for the study. The data were collected with the help of structured questionnaire schedule through personal interview method. The statistical methods used for the analysis of the data were coefficient of correlation and multiple regressions. Results showed that the variables like education level, asset possession, extension contact and mass media exposure are positively and significantly correlated with the social empowerment of women. In multiple regression analysis, education has been found to be significantly and positively characterizing towards the social empowerment of the women SHG members whereas the variable mass media exposure was significantly and negatively characterizing towards the social empowerment of the women. The R value being 0.669, it is also to infer that the selected predictor variables put together have explained 66.90 per cent variation embedded with the predicted variable, social empowerment of women after joining SHGs.